Ruthenium (II) phosphine/picolinate complexes as antimycobacterial agents - Pavan, Fernando Rogério [UNESP]; Von Poelhsitz, Gustavo; do Nascimento, Fabio B.; Leite, Sergio R. A. [UNESP]; Batista, Alzir A.; Deflon, Victor M.; Sato, Daisy N.; Franzblau, Scott G.; Leite, Clarice Queico Fujimura [UNESP] (Elsevier France-editions Scientifiques Medicales Elsevier, 2010)
The synthesis, characterization and the anti-Mycobacterium tuberculosis (MTB) activities of three ruthenium complexes containing the 2-pyridinecarboxylic acid anion (picolinate), with formulae cis-[Ru(pic)(dppm)(2)]PF(6) (1), Cis- [Ru(pic)(dppe)(2)]PF(6) (2) and [Ru(pic)(2)(PPh(3))(2)] (3) [pic = 2-pyridinecarboxylate; dppm = bis(diphenylphosphino)methane: dppe = 1,2-bis(diphenylphosphino)ethane; PPh(3) = triphenylphosphine] are reported in this article. The complexes were characterized by elemental analysis, spectroscopic and electrochemical techniques. Their in vitro anti mycobacterial activity was determinated as the Minimum Inhibitory Concentration (MIC) for MTB cell growth, measured by the REMA method. The best MICs were found for complexes (1) and (2), with values of 0.78 and 0.26 mu g/mL, respectively. The results are comparable to or better than "first line" or "second line" drugs commonly used in the treatment of TB. (C) 2009 Elsevier Masson SAS. All rights reserved.
Keywords: Antimycobacterial agents; Mycobacterium tuberculosis; REMA; Ruthenium (II) Complexes; Phosphines; Picolinate